2020
DOI: 10.1071/ah19055
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening teamwork capability in allied health: implementation of a team development program in a metropolitan health service

Abstract: ObjectiveCollaborative practice is critical to optimising patient outcomes in contemporary healthcare settings. Evidence suggests interprofessional learning is an effective way to develop teamwork capabilities, yet these skills are traditionally developed in professional silos, or not at all. This study evaluated the implementation of a team development program, the Team Management Systems (TMS) program, for allied health staff within a large metropolitan health service. MethodsA mixed-methods audit–quality im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Also, the participants had a medium range of job satisfaction, and there was a meaningful relation between the burnout subscales of the work time and working condition, experience, educational level [16,17]. Another study of job satisfaction in midwifery of New Zealand revealed that professional recognition is positively linked to job satisfaction for midwives, and decision-making autonomy and empowerment were shown to influence job satisfaction for midwives [18][19][20][21].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Also, the participants had a medium range of job satisfaction, and there was a meaningful relation between the burnout subscales of the work time and working condition, experience, educational level [16,17]. Another study of job satisfaction in midwifery of New Zealand revealed that professional recognition is positively linked to job satisfaction for midwives, and decision-making autonomy and empowerment were shown to influence job satisfaction for midwives [18][19][20][21].…”
Section: Discussionmentioning
confidence: 95%
“…Job satisfaction is an important parameter of not only employee well-being but also organizational success. Numerous Vol.7 • No.3• September 2021 studies of quality management demonstrated that there is positive associations between employee job satisfaction and quality management [20][21][22][23]. A cross-sectional survey of midwives who work in a tertiary maternity hospital in Australia showed that about half (53%) had a negative attitude about their professional support and client interaction (49%), and 21% felt negatively about professional development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to other research, coordination and collaboration are innovative strategies to support health care. Collaboration can foster interprofessional cooperation to generate safe and high-quality services (Wood et al, 2020).…”
Section: Mechanism Of Work Culturementioning
confidence: 99%
“…The most significant advantage of understanding the connectedness of social networks within organizations is not how to build strong ties, but the ability to extend into an organization's network to use and manage the flow of information. While it is essential to acknowledge that instances exist in organizations where work silos thrive, the preponderance of the extant literature provides evidence supporting integrated and crossfunctional teams to enhance the capability, effectivity, decision-making, and knowledge Enhancing student understanding of networks transfer (Fiol, 1996;Kraaijenbrink, 2012;Koohang, Koohang, Paliszkiewicz, Paliszkiewicz, Goluchowski & Goluchowski, 2017;Lara, S anchez & Villalobos, 2019;Wood, Grudzinskas, Ross, Bailey, Gordon, Burton & Wishart, 2020). An understanding of networks can provide employees with leadership and managerial advantages that could enhance their careers and position them for new job opportunities (Granovetter, 1973;Cross & Parker, 2004).…”
Section: Theoretical Foundationsmentioning
confidence: 99%